The mall selection using Analytical Hierarchy Process (AHP) approach / Nur Fayyadhah Md Din, Nur Khairiyah Amran and Rosliza Muain - Md Din, Nur Fayyadhah; Amran, Nur Khairiyah; Muain, Rosliza (2019)
In this study, an attempt has been made to study the preferable mall selection among respondents by using AHP method. The objective of this study is to determine the most important criteria that considered during the mall selection and to determine the most preferred mall among respondents. This model can assist the customers in identifying malls that most likely to deliver satisfactory to them. An ARP-based model is tested in this study by using a hypothetical scenario in which malls are evaluated. The criteria used for mall selection in the model are identified, and the significance of each criterion is determined using questionnaire. Comparisons are made by ranking the aggregate score of each mall based on each criterion, and the mall with the highest score is deemed the best. The result is evaluated by using an excel spreadsheet. The result shows that the most important criteria in this study is facilities and the most preferred mall among respondents is AEON. Although the technique may be applied in selection of any form of accommodation, but the result may not be generalized due to limitation in geographical coverage and small population.